PSYCHO-STIMULANTS FOR DEPRESSION: A SYSTEMATIC REVIEW OF EVIDENCE FROM RANDOMISED CONTROLLED TRIALS. Issue 1 (1st March 2013) - Candy, B; Jones, L; Leurent, B; Tookman, A; King, M
Abstract : Introduction: Symptoms of depression are common, disabling, and costly. In palliative care, where such symptoms may be considered unavoidable, they can go untreated. Antidepressants are not always effective and in palliative care may not be suitable. Psycho-stimulants are most commonly used in palliative care to treat opioid induced somnolence. They are known for elevating mood and reducing fatigue, and may offer an alternative to antidepressants. In 2006 we undertook the first systematic review of psycho-stimulants for depression (Candy 2008). We found, despite identifying 24 trials, inconclusive evidence on whether psycho-stimulants work. Since this review there have been new trials. Adding their findings to our earlier analyses may provide more of a definitive answer on the effect and safety of psycho-stimulants. Aims and Methods: To update our systematic review of randomised controlled trials on the effectiveness of psycho-stimulants for the symptoms of depression. Results: To date we have identified six new trials. These trials appear of better quality in reporting than many of the earlier trials. Preliminary analysis that combines the findings of the new trials with those found earlier, suggests the evidence on the impact and safety of psycho-stimulants in the treatment of symptoms of depression may be clearer. Conclusions: By March 2013 we will have completed our update. Our new findings will provide more information on whether psycho-stimulants can be classed as an alternative to antidepressants. Our findings will also provide up-to-date information on whether or not there is a need to invite more patients to undergo further trials.